Are NHS primary care performance indicator scores acceptable as markers of general practitioner quality? - Houghton, Guy (Oxford University Press, 2004)
Background: In 2002 the Department of Health published a list of 20 indicators to judge the performance of the 302 primary care organisations (PCOs) in England during 2001–2002. General practitioners (GPs) have expressed doubts about the relevance, applicability and evidence base of these indicators for actual practice. Aims: To fashion NHS performance indicators to be acceptable and relevant to practicing GPs. Design of study: A Delphi technique followed by simple mathematical modelling. Methods: We asked a group of 24 senior GP educators to place the Department of Health performance indicators in rank order as markers of quality in general practice. We found just seven indicators comprised 73% of the markers chosen and all seven were chosen by over three-quarters of the responders. Using a simple ‘sign test’ system, we then calculated a composite points score for all 302 PCOs. Results: We found that there were almost twice as many PCOs at the upper and lower ends of performance and fewer in the middle than we predicted theoretically. The results suggest that pan-PCO or practice factors account for the low performance scores of 16 of 35 PCOs with extremely poor performance and for the high scores of 17 of the 36 PCOs with extremely high performance. Conclusion: We have developed a method that shows how numerous Department of Health performance indicators can be merged into a single composite performance score. We show that this composite performance score is easy to derive, simple to interpret, is acceptable to GPs, and has face validity.